NATIONAL MENTALITY AND LANGUAGE: SPANIARDS AND SPANISH - VALERY Iovenko (Ибероамериканские тетради)
The article examines a correlation between the concepts “national mentality” and “national language”: mutual influence, Spanish manifestations of ethnic and cultural stereotypes which are peculiars to the Span-ish worldvision, translation’s application.